FAKTOR–FAKTOR PENYEBAB ALIH FUNGSI LAHAN PERTANIAN DI KECAMATAN TOMOHON SELATAN KOTA TOMOHON - Mechri Defrid Badoa; Gene H. M. Kapantow; Eyverson ., Ruauw (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the factors that affect the conversion of agricultural land in South Tomohon Subdistrict Tomohon City. In particular, this study looks at internal factors that affect the conversion of agricultural land in South Tomohon Sub-District, Tomohon City. This study was conducted by using secondary data obtained from BPS (Statistics Bureau) office Tomohon City, Subdistrict office and Village Offices in South Tomohon Sub-district. And for the primary data obtained from the direct interview with the farmers. The data is then analyzed by using qualitative data analysis techniques using tables and described descriptively. The results of research showed that land function change happened in this area, allot of land that is as housing (70%). Furthermore, for the main cause of landowners sell or alter the function of agricultural land that is due to the cost of child education and high selling prices.*jnkd*.